Temperature characteristics of FinFET based on channel fin width and working voltage - Yousif Atalla; Yasir Hashim; Abdul Nasir Abd. Ghafar; Waheb A. Jabbar (Institute of Advanced Engineering and Science, 2020)
This paper shows the temperature sensitivity of FinFET and the possibility of using FinFET as a temperature Nano sensor based on Fin width of transistor. The multi-gate field effect transistor (MuGFET) simulation tool is used to examine the temperature effect on FinFET characteristics. Current-voltage characteristics with various temperatures and channel Fin width (WF= 5,10,20,40 and 80 nm) are at first simulated, the diode mode connection has been used in this study. The best temperature sensitivity of the FinFET is has been considered under the biggest ∆I at the working voltage VDD with range of 0–5 V. According to the results, the temperature sensitivity increased linearly with all the range of channel Fin width (5-80 nm), also, the lower gate Fin width (WF=5nm) with higher sensitivity can achieved with lower working voltage (VDD=1.25 V).